CHARACTERISTIC OF TRADITIONAL GASTRONOMY IN THE FUNCTION OF CREATING TOURIST LOYALTY TOWARDS THE DESTINATION - Tamara Vujić; Drago Cvijanović; Milan Vujić (Ekonomika Poljoprivrede (1979))
Gastronomy has the power to attract tourists as a tourist attraction and make them loyal to it. Toward discussing their research, the authors first base their hypothesis on the argument that traditional gastronomy creates loyalty toward the destination. In order to test the initial hypothesis, it was necessary to answer the question, “In what way does gastronomy create a sense of loyalty toward the destination”? The results revealed that there was a unique formula in which the degree of loyalty of tourists toward travel destination directly depends on the factor of a “gastronomic experience.” The higher this factor was rated, the more the degree of loyalty toward the destination increased. Mostly, it is done by tradition, culture, authenticity, uniqueness, ambiance, and quality of food, beverages, and services. That is, the original and unique gastronomic experience of the destination which is first and foremost introduced by traditional gastronomy.